Uncertainty-Tolerant Harmonic Meter Placement in Power Systems With High Penetration of Harmonic Sources - Ahmadreza Eslami; Michael Negnevitsky; Evan Franklin; Sarah Lyden (IEEE Access)
In modern power systems, the prevalence of harmonic distortion mandates robust monitoring. Harmonic monitoring faces formidable challenges due to significant uncertainties in measurements, network parameters, and the varying nature of harmonic sources alongside the limited deployment of harmonic meters and inaccessible nodes. A remedy involves the development of potentially uncertain voltage/current pseudo-meters. This paper proposes a novel probabilistic observability method used to estimate harmonic states within defined ranges with a confidence level. Subsequently, network buses are classified into three zones with regard to their harmonic state values being above, below, or uncertain relative to harmonic limits. Leveraging this approach, the number of actual harmonic meters, indicative of monitoring system cost, the bus misclassification index and the probability of misestimating harmonic states considering harmonic limits are minimized. The uncertainties in measurements, network parameters and varying outputs of harmonic sources are addressed. The developed monitoring system is capable of truly identifying buses with harmonic states violating or likely to violate harmonic limits (hot-spots). Demonstrations on IEEE 14-bus test system, IEEE 118-bus test system and the field measurements from the Tasmanian transmission network attest to the method’s efficacy, scalability and generalization capability, while considering high uncertainty in harmonic monitoring with fewer meters than the number of harmonic states. Comparative analysis with other HSE techniques and evaluation of the computational requirements of the proposed method demonstrate both its superiority and robustness. The proposed method provides a promising cost-effective approach for harmonic monitoring in modern power systems with high penetration of distributed harmonic sources.